1984
DOI: 10.1057/palgrave.jibs.8490470
|View full text |Cite
|
Sign up to set email alerts
|

The Korean Manufacturing Multinationals

Abstract: As an extension of the export-led growth of national economy overseas, direct investment by Korean multinationals has been rapidly increasing. This article explores the development of the overseas manufacturing direct investment by Korean firms and the relationship between parent firms and overseas affiliates. Three main issues are discussed: the ownership-specific assets, location-specific factors, and government policies are the important sets of variables that help to explain the internationalization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 0 publications
0
31
0
1
Order By: Relevance
“…While in most studies dealing directly with the internationalization of emerging economies, multinationals have been centered on Asian companies (Buckley and Mirza, 1988;Chen and Chen, 1998;Collinson and Rugman, 2007;Goldstein, 2009;Kumar and Kim, 1984;Matthews, 2006;Pangarkar, 1998;Ramstetter, 1999;Yeung, 2000), or on other Latin American countries such as Brazil, Chile and Mexico. This paper offers a contribution to the internationalization literature of companies from a specific and under-researched Latin American country: Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…While in most studies dealing directly with the internationalization of emerging economies, multinationals have been centered on Asian companies (Buckley and Mirza, 1988;Chen and Chen, 1998;Collinson and Rugman, 2007;Goldstein, 2009;Kumar and Kim, 1984;Matthews, 2006;Pangarkar, 1998;Ramstetter, 1999;Yeung, 2000), or on other Latin American countries such as Brazil, Chile and Mexico. This paper offers a contribution to the internationalization literature of companies from a specific and under-researched Latin American country: Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has investigated chiefly the effects that a country's structure has on the country's economic growth in order to explain the development of the country itself. Kumar and Kim (1984) found that the amount of the outflow of FDI from Asian newly industrialized economies to developed countries has rapidly increased over the past decade. Emerging economy firms investing in developed countries have tended to use outward FDI primarily to obtain intangible assets.…”
Section: Factors Causing Changes In Outward Fdimentioning
confidence: 99%
“…In reality, firms from emerging countries investing in developed countries use outward FDI to strengthen their non-price competitiveness (Kumar and Kim 1984). Moreover, foreign firms invest for strategic asset-seeking purposes in developing countries when the firms want to attain a specific asset such as a particular technology although the investments are not immediately profitable.…”
Section: Efficiency-seeking Outward Fdimentioning
confidence: 99%
“…Korea is the second largest investor in the US (Zeile 2004), so the general topic of Korean firm activity in the US has obvious importance. Additionally, however, the simultaneous examination of chaebol and non-chaebol firm activity is also an important addition to FDI analysis where this country is concerned, specifically because of the historical factors governing the genesis and trajectory of Korean firm FDI efforts as shaped by government policy (see Kumar and Kim 1984).…”
Section: Theory and Cluster Considerationsmentioning
confidence: 99%
“…Data on Korean investment in the US was collected from a postal survey administered in mid-2004 that targeted Korean subsidiaries with HQs located in Korea that perform either production or marketoriented functions in the US, primarily because largescale Korean FDI to the US has generally served to augment their domestic production and sales (Kumar and Kim 1984;Jyoung 1997). A list of US subsidiaries list was obtained fom the Korean Chamber of Commerce and Industry (KOCHAM) directory, one of the most comprehensive databases on Korean firms and their activities in the US Initially, a database of 115 firms was compiled, but fourteen firms did not have a parent company in Korea or were in the process of withdrawing their investment from the US.…”
Section: Data and Surveymentioning
confidence: 99%